STUDY OF EFFECTS OF LUNAR TIDAL WAVE PASSAGE IN UPPER ATMOSPHERE OF EARTH ACCORDING TO MONITORING DATA AT RADIO TELESCOPE «URAN-4» RI NANU - Ryabov, M. I.; Sobitnyak, L. I. (Одеські астрономічні публікації, 2019)
The paper examines data on the effects of the lunar tidal wave in the Earth ’s upper atmosphere on the observed flux of radio sources. Monitoring of the fluxes of powerful galactic and extragalactic radio sources is carried out at the URAN-4 radio telescope of the Odessa Observa- tory of the Institute of Radio Astronomy of the NAS of Ukraine since 1987 till now. The monitoring program in- cludes radio galaxies 3C274, 3C405 and supernova rem- nants 3C144, 3C461. Changes of fluxes of radiation sources at decameter waves are determined by the condi- tion of an ionosphere resulted due to space weather varia- tion and tidal events. When radio sources are observed through a tidal wave, a "plasma lens" effect is realized in the ionosphere. Depending on the position of the radio source relative to the tidal wave, the radiation wave front is sought. As a result, various effects are realized: strong fo- cusing, intense flickering or "blurred" recording of the ra- dio source. According to the data of radiation monitoring of powerful radio sources, the dimensions and structure of the tidal wave zone in the upper atmosphere producing the effect of "plasma lensing" have been determined. The total size of this zone according to observations on frequent 20 and 25 MHz is on the order of 30-60 angular degrees in right ascension and declination.